Cross-sector Collaboration Process in Increasing the Human Development Index in Tambrauw Regency - Woria, Mousche Willems Jullians; Ibrahim, Muh. Akmal; Musa'ad, Muhammad (KnE Social Sciences, 2025)
The Human Development Index (HDI) is very important in showing a comprehensive picture of the quality of life of people in a region. In order to improve the HDI, a collaborative approach is needed, but the process needs to be ensured to run well. Therefore, this study aims to analyze and explore the collaborative process in improving the HDI in Tambrauw Regency. This study uses qualitative methods to be able to explain the research phenomenon according to its context. This study focuses on the collaboration process in achieving three indicators of the HDI, namely economy, health and education. Primary data sources were obtained from interviews with all stakeholders in an effort to improve the HDI. The results of this study obtained the fact that the collaboration process in the development of the HDI was not optimal. Basically, the regional apparatus organizations that collaborated designed a joint agreement to work together to improve the HDI, but it was not accompanied by a commitment in the form of real action. The political will of formal and informal leaders in the form of policy and budget support still needs to be improved. The process of building legitimacy was not accompanied by forming a collaboration-based team between regional apparatus organizations so that synergy could be built together. All regional apparatus organizations that collaborated trusted each other in working to improve the HDI so that conflicts rarely occurred. Program planning, improving the HDI refers to the Regional Medium-Term Development Plan (RPJMD).